1992
DOI: 10.1007/bf00012016
|View full text |Cite
|
Sign up to set email alerts
|

Can maize cultivars with low mineral nutrient concentrations in the grains help to reduce the need for fertilizers in third world countries?

Abstract: An earlier study revealed considerable genotypic variation in grain N, P and K concentrations (GNC, GPC and GKC, respectively) in tropical maize. The expression of varietal differences in GNC, GPC and GKC, however, may depend on environmental conditions such as the N status of the soil. Two tropical maize hybrids (Suwan 2301 and CP 1) with comparable yielding capacity, but contrasting GNCs, GPCs and GKCs, were therefore grown at four levels of N in a field experiment at Farm Suwan (Thailand, latitude 14.5°N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…The application of N increased P uptake, with the exception of a few hybrids in Embu. Feil et al ( 1992 ) and Holou et al ( 2011 ) also found that N fertilizer applications increased P uptake consistently in continuous maize cropping systems. The application of N fertilizer has been found to increase root branching, particularly closer to the surface where P levels are highest (Postma et al 2014 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The application of N increased P uptake, with the exception of a few hybrids in Embu. Feil et al ( 1992 ) and Holou et al ( 2011 ) also found that N fertilizer applications increased P uptake consistently in continuous maize cropping systems. The application of N fertilizer has been found to increase root branching, particularly closer to the surface where P levels are highest (Postma et al 2014 ).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is important to look at the status of multiple nutrients at once. Globally, studies have looked at the impact of N fertilizer on the uptake of non-N nutrients such as phosphorus (P), potassium (K), and sulfur (S) (Feil et al 1992 ; Holou et al 2011 ; Ciampitti et al 2013 ) and micronutrients (Ciampitti and Vyn 2013 ), but no such studies exist in SSA. These global studies have primarily focused on higher N fertilizer rates than what is typically applied in SSA, limiting the direct applicability of their findings to smallholder farmers in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…This could change if (i) more Nresponsive genotypes are cultivated or (ii) the soil becomes deficient in P and K. Some experiments conducted at Farm Suwan revealed individual grain yield responses of indigenous cultivars to N fertilization (THIRAPORN et al 1987, FEIL et al 1991. Cultivar by N fertilization interactions in grain yield were paralleled by cultivar by N fertilization interactions in G P C and G K C (FEIL et al 1991 b). This indicates that a more efficient conversion of high N rates into grain yield would decrease the G P C and GKC.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrações e conteúdos de P nos grãos de milho de germoplasma tropical semelhantes foram verificados por FEIL et al (1992), em cujo trabalho havia elevado teor de P disponível no solo e o nível de adubação nitrogenada foi o mesmo empregado neste ensaio. No estudo de FEIL et al (1992), os sabugos também apresentaram o menor conteúdo de P e, pela literatura, tem-se que a remobilização a partir deles, bem como a do colmo e palha da espiga, precede à das folhas (GORSLINE, 1965;CLARK, 1975).…”
Section: Avaliação De Variedades De Milho Para Eficiência Ao Fósforo unclassified